Age and vaccine information sources drive vaccine hesitancy: A household survey in Central-Western Brazil - Ana Isabel do Nascimento; Danilo dos Santos Conrado; Lisany Krug Mareto; Micael Viana de Azevedo; João Cesar Pereira da Cunha; Gabriel Serrano Ramires Koch; Laysa Gomes Osório; Samara Tessari Pires; Letícia Suemi Arakaki; Sara Raquel Pinto Borges; Robson Franca Gomes e Silva; Rodrigo Mayer Pucci; et al. (PLoS ONE, 2026)
In recent decades, the decline in vaccination coverage has garnered global attention, and the impact of vaccine hesitancy has become a significant concern for public health policymakers worldwide. This study aims to measure vaccine hesitancy and its associated factors among residents of Campo Grande, Mato Grosso do Sul, Brazil. From September 2022 to October 2023, a cross-sectional study aligned with a household survey was conducted to measure vaccination coverage among residents of Campo Grande municipality in Brazil. Data were collected through face-to-face interviews using the WHO. Reasons for vaccine hesitancy were classified under the 3C conceptual model of vaccine hesitancy determinants. Descriptive statistics were employed to characterize the study population, and univariate and multivariate logistic regression analyses were conducted to assess the association between hesitant and non-hesitant participants and the study variables. We included 467 households in the study, with a total of 518 participants interviewed. Over half of the participants hesitated to get vaccinated (50.2%), with the COVID-19 vaccines being the most hesitated (55.4%). The majority of reported reasons for hesitancy were related to a lack of confidence (62.3%). The hesitant participants in our study were younger than the non-hesitant participants (aOR = 0.98; 95% CI: 0.97, 0.99), were less likely to believe that vaccines could protect themselves and their children from serious diseases (aOR = 0.23; 95% CI: 0.06, 0.66), and were less likely to get information from healthcare workers or official health organizations’ online profiles (aOR = 0.39; 95% CI: 0.17, 0.86). We observed a high prevalence of vaccine hesitancy in Campo Grande. The results highlight the potential impact of the COVID-19 pandemic and the infodemic in increasing negative feelings about vaccines.